Stringy approach to the Minimal Supersymmetric Standard Model - Malyuta, Yu.M.; Obikhod, T.V. (Вопросы атомной науки и техники, 2010)
Superstring theory is applied to construct the Minimal Supersymmetric Standard Model. The mass spectrum, partial widths and production cross sections of superpartners are calculated. This approach gives concrete predictions for superpartner searches at the LHC.